Design of soil moisture distribution sensor based on high-frequency capacitance - Hua, Yan; Zejun, Tang; Zhen, Xing; Dingneng, Gao; Haoxing, Hong (International Journal of Agricultural and Biological Engineering, 2016)
In order to obtain accurate real-time soil moisture data and the spatial distribution of soil moisture, the soil moisture measurement methods based on high-frequency capacitance edge field effect were analyzed, the structure of probe was studied, and a multi-channel soil moisture sensor was designed. Moreover, with the established two-dimensional trace planar capacitance probe model and the method of the finite element analysis, relationship between the structure of sensor probe and electric field intensity was studied and capacitance of the probe trace amount planar capacitance model was analyzed, the most optimal structure of sensor probe was determined. Design parameters of the probe which can achieve optimal sensitivity and detection range are: outer diameter 40 mm and inner diameter 38.4 mm for the probe copper ring electrode, axial length 20 mm and axial spacing 10 mm. The sensor is suitable for measuring the moisture of different type of soil. Moreover, the features of the profile soil moisture sensor were experimentally explored. The measurement accuracy reached ±1.31% with better stability and consistency. Sensor probes can be assembled according to the measurement depth and used to measure soil moisture of different crop root zone. Keywords: high frequency capacitance detection, profile, soil moisture sensor DOI: 10.3965/j.ijabe.20160903.2226 Citation: Yan H, Tang Z J, Xing Z, Gao D N, Hong H X. Design of soil moisture distribution sensor based on high-frequency capacitance. Int J Agric & Biol Eng, 2016; 9(3): 122－129.